Working for man : The demestication of animals - Hyams , Edwards; Gregory , Peter (London : Kestrel Books, 1975)
Working for Man: The Domestication of Animals explains how humans domesticated animals over thousands of years and how this changed human life. The book shows how animals were used for food, farming, transport, and labor, and how this partnership helped humans develop agriculture, settlements, and civilizations.